Venomous Snakes Reveal Ecological and Phylogenetic Factors Influencing Variation in Gut and Oral Microbiomes - Smith, Sierra N.; Colston, Timothy J.; Siler, Cameron D. (Frontiers in Microbiology, 2021)
The gastrointestinal tract (GIT) of vertebrates contains a series of organs beginning with the mouth and ending with the anus or cloacal opening. Each organ represents a unique environment for resident microorganisms. Due to their simple digestive anatomy, snakes are good models for studying microbiome variation along the GIT. Cloacal sampling captures the majority of the microbial diversity found in the GIT of snakes—yet little is known about the oral microbiota of snakes. Most research on the snake mouth and gut microbiota are limited to studies of a single species or captive-bred individuals. It therefore remains unclear how a host’s life history, diet, or evolutionary history correlate with differences in the microbial composition within the mouths and guts of wild snakes. We sampled the mouth and gut microbial communities from three species of Asian venomous snakes and utilized 16S rRNA microbial inventories to test if host phylogenetic and ecological differences correlate with distinct microbial compositions within the two body sites. These species occupy three disparate habitat types: marine, semi-arboreal, and arboreal, our results suggest that the diversity of snake mouth and gut microbial communities correlate with differences in both host ecology and phylogeny.